Earth story [video recording]. ([sl.]: [sn.])
Unravel the secrets of our planet. Using a combination of breathtaking images of natural world and state-of-the-art graphics, this astonishing series takes us to locations all over the world. From the bottom of the atlantic Ocean to the Polar ice-cap; into the crater of an active volcano and up to the highest peaks of the Himalayas, Earth story follows the scientists as they piece together the clues that reveal the secrets of our planet and the life it sustains.